(Staying with) the trouble with tourism and travel theory?. (March 2021) - Ren, Carina
It has now been 20 years since Adrian Franklin and Mike Crang's The trouble with tourism and travel theory? introduced the first volume of Tourist Studies. In the year of 2001, business-oriented approaches to studying tourism were thriving due to the rapid growth of tourism. In their diagnosis of tourism research of the day, Franklin and Crang pointed to the lack of theory and "a tendency for studies to follow a template, repeating and reinforcing a specific approach" (p. 6) as the fundamental trouble with the academic commitment to tourism. The twentieth anniversary issue of Tourist Studies offers an occasion to return to this analysis of tourism research and explore what the "trouble" with knowing and thinking about tourism might be today? Where do we go, where do we look, and whom do we listen to and learn from to know about tourism? And how may we work to improve our sensibilities toward knowing tourism?